Rigidochromic conjugated polymers carrying main-chain molecular rotors. Issue 77 (9th September 2019) - van der Scheer, Pieter; van Zuijlen, Quintin; Sprakel, Joris
Abstract : We design and prepare rigidochromic conjugated polymers that carry molecular rotors in the main chain. We show how a suitable design maintains the mechanosensitivity of the rotors upon incorporation into an extended π-conjugated system. Abstract : We design and prepare rigidochromic conjugated polymers that carry molecular rotors in the main chain. We show how a suitable design maintains the mechanosensitivity of the rotors upon incorporation into an extended π-conjugated system. Construction of donor–acceptor polymers enables their use as ratiometric probes for polymer micromechanics, which we evidence through micromechanical imaging of a phase-separated polymer blend.